CompTIA advanced security practitioner : (CASP+) CAS-004 cert guide - McMillan, Troy (Pearson IT Certification, 2023)
CompTIA Advanced Security Practitioner (CASP+) CAS-004 Cert Guide presents you with an organized test preparation routine through the use of proven series elements and techniques. Exam topic lists make referencing easy. Chapter-ending Exam Preparation Tasks help you drill on key concepts you must know thoroughly. CompTIA Advanced Security Practitioner (CASP+) CAS-004 Cert Guide focuses specifically on the objectives for the CompTIA Advanced Security Practitioner (CASP+) CAS-004 exam. Leading expert Troy McMillan shares preparation hints and test-taking tips, helping you identify areas of weakness and improve both your conceptual knowledge and hands-on skills. Material is presented in a concise manner, focusing on increasing your understanding and retention of exam topics.